Religion and Philanthropy: Islamic Teaching During the Israel-Palestine Conflict - Farida, Anis; Sulaiman, Sulaiman; Airlangga PH, Ahmad Rahmatullah; Mufidah, Azizah Rizqi; Bustomi, Yazid Imam (Al-Albab, 2024)
Religious teachings are essential to note in seeing the phenomenon of massive Islamic social movements that occur around the world and awareness of a humanitarian movement based on dogmatic values and moral foundations. Previous studies have not explored the aspect of religious teachings on Islamic social movements in the context of armed conflict, so this research must be carried out. Previous studies have focused more on antitheses to misinterpretations of Islamic teachings and less on accommodating philanthropic perspectives in war analysis and macro implications in the digital age. This study covers the interpretation of Islamic teachings that encourage philanthropy, Islamic social movements, and morality-based solidarity in response to the Israeli-Palestinian conflict. The desk research method is used to collect data through the Quran, Hadith, social media, and library research. The stages of analysis include the interpretation of the postulates that encourage philanthropy, the perspective of social movements, and fundamental moral theories to provide a holistic picture of the phenomenon of Islamic philanthropy in the digital era. The findings of this study include the conclusions of Islamic religious teachings that invite Muslims to do philanthropy, the internalization of religious teachings as a driver of Islamic social movements, and moral encouragement that influences an actor’s action in doing philanthropy. The resulting recommendations involve the collaboration of state institutions with all levels of society to ensure security and increase legitimacy in conducting fundraising and providing assistance to victims of armed conflict in Palestine.